2021
DOI: 10.1111/apha.13700
|View full text |Cite
|
Sign up to set email alerts
|

High‐intensity exercise in hypoxia improves endothelial function via increased nitric oxide bioavailability in C57BL/6 mice

Abstract: Aim The optimal exercise intensity to improve endothelial function remains unclear, as well as whether the addition of hypoxia could potentiate this function. Therefore, the aim of this study was to compare the effects of different exercise intensities in normoxia and hypoxia on vascular reactivity and nitric oxide (NO) bioavailability in mice. Methods C57BL/6 mice underwent treadmill running three times per week, for 4 weeks at either low, maximal or supramaximal intensity in normoxia or hypoxia (inspire oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Combination of several environmental stressors is also investigated ( 74 ). Some mechanisms explored in sport lead to clinical advancements [e.g., RSH-induced compensatory vasodilation that may be of interest in angiology for treatment of patients with endothelial dysfunction ( 75 )]. Intermittent hypoxic conditioning, have been implemented for general health purposes or in clinical populations, for example in patients with diabetes ( 76 ) or neurodegenerative diseases ( 77 ).…”
Section: Dose-response To Exercisementioning
confidence: 99%
“…Combination of several environmental stressors is also investigated ( 74 ). Some mechanisms explored in sport lead to clinical advancements [e.g., RSH-induced compensatory vasodilation that may be of interest in angiology for treatment of patients with endothelial dysfunction ( 75 )]. Intermittent hypoxic conditioning, have been implemented for general health purposes or in clinical populations, for example in patients with diabetes ( 76 ) or neurodegenerative diseases ( 77 ).…”
Section: Dose-response To Exercisementioning
confidence: 99%
“…The underlying mechanism of high-intensity exercise improving peak VO 2 in patients with CAD may be related to the fact that high-intensity exercise can stimulate muscle vascularization, improve blood circulation, and enhance blood oxygen-carrying capacity ( 45 ); In addition, studies ( 46 ) have shown that higher intensity exercise can stimulate the pumping capacity of the heart to a greater extent, increase blood flow, increase endothelial shear stress, activate endothelial nitric oxide synthase, and increase antioxidant status. Thus, nitric oxide synthesis is improved and its bioavailability is increased, which consequently improves the vascular endothelial function ( 47 49 ). High-intensity exercise can also increase oxisome proliferator-activated receptor γ coactivator 1α (a regulator of mitochondrial biogenesis) to improve mitochondrial function and enhance rapid adaptation and metabolic capacity in skeletal muscles ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent adaptation has beneficial effects on improving metabolic health and cardiorespiratory fitness. 9,10 Exercise can be divided into (1) acute exercise (at least 1-5 days of exercise) and (2) long-term exercise in terms of the phase of activity.…”
Section: Exercise-mediated Autophagy In Cardiovascular Diseasesmentioning
confidence: 99%
“…As a non‐pharmacological and non‐traumatic intervention, exercise initiates a multitude of processes aimed at restoring physiological homeostasis. Subsequent adaptation has beneficial effects on improving metabolic health and cardiorespiratory fitness 9,10 . Exercise can be divided into (1) acute exercise (at least 1–5 days of exercise) and (2) long‐term exercise in terms of the phase of activity.…”
mentioning
confidence: 99%